Analysis of low isolation problem in HMC using Ishikawa model: A case study. (February 2018) - Jayaprasad, G.; Dhanalakshmi, P.P.; Baskaran, M.; Hemachandran, S.
Abstract: Electronics systems for space application always demand higher performance, weight saving and volume diminution etc. without sacrificing their reliability. As part of this stringent requirement, a few circuit blocks which are repeatedly used in various inertial systems are being realized in Hybrid Micro Circuits (HMCs). Recently, a few batches of HMCs fabricated by a specific vendor showed low electrical isolation between the HMC package body and other functional pins at ambient temperature. However, the electrical isolation values were found to be normal at elevated temperatures. The low electrical isolation was causing leakage current between pins or package body to other pins. This makes the performance of the HMCs unpredictable during its operational period. In this paper, study and analysis conducted with respect to the low electrical isolation observed in HMCs are discussed. Root cause of the problem was analyzed by conducting methodical and systematic tests based on a formulated Ishikawa model. The major tests conducted in this analysis include external visual inspection, isolation measurements, Scanning Electron Microscopy (SEM), leak tests, Residual Gas Analysis (RGA), internal visual inspection etc. Based on the test results, root cause of the isolation problem was narrowed down to process related, which was one of the primary causes as stipulated in Ishikawa model. The real cause of the problem was the formation of ammonium hydroxide inside the HMC due to the presence of ammonia and moisture. The defective HMCs showed very large quantity of these conducting residues inside the HMCs during the RGA test. These residues emanated from the epoxy material used to attach the alumina substrate in the HMC. These faulty HMCs have not undergone vacuum baking properly before being sealed due to faulty functioning of the chamber. Hence residual gases and moisture could not be outgassed completely before sealing. Internal visual inspection of the HMCs revealed spill over of substrate attach epoxy to the Glass To Metal Seal (GTMS) thereby bridging the package pin and HMC body. Ammonium hydroxide present in this bridged epoxy was causing the low electrical isolation at ambient condition. The electrical isolation that resulted from the ammonium hydroxide is quantified and the results were found comparable with the measured values. At elevated temperatures, the ammonium hydroxide again decomposes to ammonia and water vapor and loses its conductivity and the isolation values become normal. Highlights: A few batches of HMCs fabricated by a vendor showed low electrical isolation between package header and pin Root cause analysis was carried out based on an Ishikawa model developed which operated by conducting several tests such as inspection, measurements, leak, SEM, RGA RGA reported large quantity of Ammonia and Moisture inside problem reported HMCs due to improper baking of the HMC packages Ammonium Hydroxide present over the epoxy bridged the HMC pin & body led to low electrical isolation